Coupling of Skyrmions Mediated by the Rkky Interaction - Altbir-Drullinsky, D (American Institute of Physics, 2018)
A discussion on the interaction between skyrmions in a bi-layer system connected by a non-magnetic metal is presented. Using a free charge carrier model, we have shown that, depending on the spacer thickness, the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction can induce attractive or repulsive interactions. We have also shown that due to an increase in the RKKY energy when the skyrmions are far from each other, their widths are diminished. Finally, we have obtained analytical solutions to the skyrmion position when the in-plane distance between the skyrmions is small. In this case, an attractive RKKY interaction yields a skyrmion precessional motion. This RKKY-induced coupling could be used as a skyrmion drag mechanism to displace skyrmions in multilayers. © 2018 Author(s).